2011
DOI: 10.3109/19396368.2011.562960
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sperm nuclear protein gene polymorphisms and DNA integrity in infertile men

Abstract: Sperm nuclear proteins, the protamines (PRM) and transition nuclear proteins (TNP) play a crucial role in sperm nuclear condensation. The compact packaging of sperm DNA by protamines maintains sperm genome integrity, which is prerequisite for normal sperm function. However the effect of nucleotide variations in PRM and TNP genes on sperm DNA integrity and male fertility is not clear. This case-control study was planned to analyze PRM and TNP gene nucleotide variations and sperm DNA integrity in 100 oligozoospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…In human sperm cells, 85% of the histones are replaced by protamine, allowing sufficient chromatin density to be achieved [7] and reducing the availability of sites that could be harmed by DNA-damaging agents [8]. Evidence indicates that a high proportion of histones in sperm relative to protamine causes defective chromatin compaction, subsequently leading to an increased risk of male infertility [9]. A proper ratio of protamine P1 to protamine P2 (normal, 0.8-1.2) is required for normal sperm function [10].…”
Section: Introductionmentioning
confidence: 99%
“…In human sperm cells, 85% of the histones are replaced by protamine, allowing sufficient chromatin density to be achieved [7] and reducing the availability of sites that could be harmed by DNA-damaging agents [8]. Evidence indicates that a high proportion of histones in sperm relative to protamine causes defective chromatin compaction, subsequently leading to an increased risk of male infertility [9]. A proper ratio of protamine P1 to protamine P2 (normal, 0.8-1.2) is required for normal sperm function [10].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the minor C allele of SNP rs2284922 is located in a conserved F-SNP (a web-based SNP analysis tool) sequence [Lee and Shatkay 2008]. A minor alteration of the conserved sequences could induce a phenotypic change [Venkatesh et al 2011;Westerveld et al 2004]. One must also consider that the variation of the SNP rs195434 in the 3 0 -UTR region might affect translational progress, as translational control in the 3 0 -untranslated region (3 0 -UTR) could influence protein level [de Moor et al 2005].…”
Section: Resultsmentioning
confidence: 99%
“…During proliferation, low level of USF1 expression in Sertoli cells limited the USF recruitment to E-box motifs within the promoter regions of Nr5a1 and Shbg genes which were vital for Sertoli cell differentiation [12], therefore the progress of the spermatogenesis might be repressed as a result of the aberrant differentiation of Sertoli cells, NOA would take place; 2) We found that the minor allele C of the SNP rs2284922 located in the conserved region of USF1 gene by means of the F-SNP database [25], a web-based SNP analysis tool. Such an alteration in the gene might lead to an abnormality of gene expression or weaken the stability of gene [26]; 3) the variation of rs2516838 might relate to the initiation of spermiogenesis. There were studies revealing that the rs2516838 polymorphism of USF1 was associated with methylation of genomic DNA [27,28].…”
Section: Discussionmentioning
confidence: 99%